Mac OS X 10.6 Snow Leopard - Williams, Robin 1953- (Peachpit Press, 2010)
The latest update of Robin Williams's bestselling guide will have you working miracles in no time with Snow Leopard, the fastest and most reliable version of the Mac OS X ever. With this book, you can learn in your own way, whether it's working through the lessons from start to finish, jumping straight to step-by-step exercises about new features, or looking up just what you need to know at that moment. There are hundreds of exciting tools and hidden gems in your Macintosh. And with the gentle, yet expert, hand of Robin Williams guiding you along the way, you will learn to take full advantage of all that Snow Leopard has to offer. If you are new to Mac OS X, you'll learn to use your Mac with help from a world-renowned teacher. From there, you can move on to customize it to suit the way you work. And if you've been using Mac OS X already, you'll learn to use all of the new features in Snow Leopard.
Print version record
Keywords: Mac OS; Operating systems (Computers); Macintosh (Computer); Systèmes d'exploitation (Ordinateurs); Macintosh (Ordinateur); operating systems